Believability of Cigarette Warnings About Addiction: National Experiments of Adolescents and Adults. Issue 7 (30th August 2017) - Lazard, Allison J; Kowitt, Sarah D; Huang, Li-Ling; Noar, Seth M; Jarman, Kristen L; Goldstein, Adam O
Abstract: Introduction: We conducted two experiments to examine the believability of three addiction-focused cigarette warnings and the influence of message source on believability among adolescents and adults in the United States. Methods: Experimental data were collected using national phone surveys of adolescents (age 13–17; n = 1125; response rate, 66%) and adults (age 18+; n = 5014; response rate, 42%). We assessed the believability of three cigarette warnings about addiction attributed to four message sources (Food and Drug Administration [FDA], Surgeon General, Centers for Disease Control and Prevention [CDC], no source). Results: The majority of adolescents and adults reported the three cigarette warnings were very believable (49%–81% for adolescents; 47%–76% for adults). We found four to five times higher odds of adolescents believing a warning that cigarettes are addictive (warning 1) or that nicotine was an addictive chemical (warning 2) compared to a warning that differentiated the addictive risks of menthol versus traditional cigarettes (warning 3), warning 1 adjusted odds ratio (aOR): 4.53, 95% confidence interval (CI): 3.10, 6.63; warning 2 aOR: 3.87, 95% CI: 2.70, 5.50. Similarly, we found three to five times higher odds of adults (including current smokers) believing the same warnings, warning 1 aOR: 3.74, 95% CI: 2.82, 4.95; warning 2 aOR: 3.24, 95% CI: 2.45, 4.28. Message source had no overall impact on the believability of warnings for either population. Conclusions: Our findings support the implementation of FDA's required warnings that cigarettes are addictive and that nicotine is an addictive chemical. These believable warnings may deter adolescents from initiating smoking and encourage adults to quit smoking. Implications: This article describes, for the first time, the believability of different cigarette warnings about addiction. We now know that the majority of adolescents and adults believe cigarette warnings that highlight cigarettes as addictive and that nicotine is an addictive chemical in tobacco. However, a warning that highlighted the relative risk of addiction for menthol cigarettes compared to traditional cigarettes was not as believable among either population. Our findings support the implementation of FDA's required warnings that cigarettes are addictive and that nicotine is an addictive chemical that may deter adolescents from initiating smoking and encourage adults to quit smoking.